Transport infrastructure: current status and development - Kryshtal, Halyna (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of the article is to identify approaches to understanding transport infrastructure and the level of human development, to determine the mechanisms of the impact of transport infrastructure on human development, to determine the mechanisms of the impact of human development on the state of transport infrastructure. The state of transport infrastructure of Ukraine is considered in detail in the article. According to the results of the study, the directions of the development of countries in terms of transport infrastructure and the level of welfare of the population are determined. The relationship between transport infrastructure and human development through the pricing mechanism has been studied. The study found out that the relationship is characterized by micro- ("transport infrastructure - pricing - human development") and macroeconomic ("pricing - transport infrastructure - human development") effects, which allowed to link this vector with the political sphere of society.Methodology: The theoretical and methodological basis of the study is represented by the scientific works of leading scientists in the field of human development, as well as the author's concept of structural and infrastructural socio-economic development. The research used such methods as analysis and synthesis, the method of historical and logical modeling. The method of formalization, the method "from the abstract to the concrete", as well as the historical method, the method of economic interpretation are used as theoretical methods in the work. From a practical point of view, the study also included the method of grouping statistical data, statistical and econometric analysis. The results of the study can be used in the field of economic policy adjustment, in the courses of economic policy, state regulation, as well as in practice for the development of socio-economic and transport policy of the state.JEL Classification: G1, L9.